1999
DOI: 10.1111/j.1574-695x.1999.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical strains ofCandida albicansexpress the surface antigen glyceraldehyde 3-phosphate dehydrogenase in vitro and in infected tissues

Abstract: We have previously described the presence of an enzymatically active form of glyceraldehyde 3-phosphate-dehydrogenase (GAPDH) in the cell surface of Candida albicans ATCC 26555 which is also a fibronectin and laminin binding protein. Immunohistochemical analysis of tissue sections from patients with disseminated candidiasis with a polyclonal antiserum to GAPDH from C. albicans (PAb anti-CA-GAPDH) revealed that the enzyme is expressed at the surface of fungal cells in infected tissues. The same PAb detected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 30 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Whereas GAP DH plays a key role in glycolysis, evidence suggests that it also can serve multiple other functions Fischetti, 1992, 1997;Alvarez-Dominguez et al, 1997;Daubenberger et al, 2003;Bergmann et al, 2004;Boël et al, 2005;Terao et al, 2006;Jin et al, 2011). In particular, GAP DH has been implicated as a ligand for cell invasion present on the surface of several pathogenic microbes and has been tested as a vaccine candidate (Gil et al, 1999;Argiro et al, 2000;Rosinha et al, 2002;Lama et al, 2009;Perez-Casal and Potter, 2016). Recent studies have identified surface expression of Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas GAP DH plays a key role in glycolysis, evidence suggests that it also can serve multiple other functions Fischetti, 1992, 1997;Alvarez-Dominguez et al, 1997;Daubenberger et al, 2003;Bergmann et al, 2004;Boël et al, 2005;Terao et al, 2006;Jin et al, 2011). In particular, GAP DH has been implicated as a ligand for cell invasion present on the surface of several pathogenic microbes and has been tested as a vaccine candidate (Gil et al, 1999;Argiro et al, 2000;Rosinha et al, 2002;Lama et al, 2009;Perez-Casal and Potter, 2016). Recent studies have identified surface expression of Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Gapdh is located both in the cytoplasm and as a surface antigen in C. albicans , and in L. prolificans secretome, cell surface and hyphae. , This protein is also important for the evasion of the host immune system by high affinity binding to regulators of complement activation such as Factor H (FH) or FH-like protein (FHL-1) .…”
Section: Discussionmentioning
confidence: 99%
“…Except for its significant role in the process of glycolysis in C. albicans, GAPDH has been identified as the cytosolic antigen on the cell wall surface which also is enzymatically active (Gil-Navarro et al, 1997). Gil et al (1999) and Delgado et al (2003) suggested that the cell wall-bound GAPDH expressed both on the surface of clinical isolates and on the fungal cells in infected host tissues. Generally, adhesion is associated with tissue invasive process and virulence in C. albicans (Gil et al, 1999).…”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
“…Gil et al (1999) and Delgado et al (2003) suggested that the cell wall-bound GAPDH expressed both on the surface of clinical isolates and on the fungal cells in infected host tissues. Generally, adhesion is associated with tissue invasive process and virulence in C. albicans (Gil et al, 1999). Because of the ability that GAPDH in C. albicans can bind hosts' fibronectin and laminin, it contributes to the progress of adhesion during candidiasis infections (Gil et al, 1999).…”
Section: Glyceraldehyde-3-phosphate Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation